(untitled) (Texas Journal of Medical Science, 2024)
Cardiac and renal diseases often coexist and patients with cardiac and renal failure have high morbidity and mortality. Cardiorenal syndromes (CRSs) are disorders of the heart and kidneys whereby dysfunction in one organ may induce dysfunction in the other organ. Five subtypes of CRSs have been defined by the Acute Dialysis Quality Initiative Consensus Group. There is a need for early detection and monitoring of patients with CRSs. Biomarkers play a key role in the diagnosis and monitoring of acute myocardial infarction, chronic heart failure, and chronic kidney disease. In recent years, new biomarkers have been identified that may play a role in the early diagnosis of acute kidney injury. Herein, we review the use of serum and urine biomarkers in the diagnosis and management of CRSs. The established cardiac and renal biomarkers such as the cardiac troponins, natriuretic peptides, urine albumin, and creatinine, as well as the new renal biomarkers cystatin C and neutrophil gelatinase–associated lipocalin are reviewed in detail. The recent advances in assay methods, clinical studies, and recommendations in clinical guidelines are discussed. With advances in biomarker research, in future, perhaps a multimarker approach will become feasible to stratify the diagnosis of CRS for individualized treatment and prognosis.